Biomass Production, its Distribution and Biological Productivity in Pinus patula, Schl and Cham Plantations in Nilgiris - Malhotra, P. P.; Tandon, V. N.; Kumar, Promod (Indian Forester, 1985)
The biomass production, its distribution by various tree components for 6, 8, 10, 12 and 14 years pld plantations of Pinus patula Schl and Cham at Ootacamund(Tamil Nadu) has been discussed. The total blomass ranges from 25 t/ha (6 years) to 260 t/ha 914 years) of which production increases with increasing age upto 10 years and thereafter slowed down gradually. Though, for comparable ages, blomass recorde at kodaikanal is much higher, but the advantage of the hardiness of the species has been properly taken by the State Forest Department and almost all the frost holes have been brought under Pinus patula. The detailed study on nutrient cycling is suggested.